2014
DOI: 10.1111/desc.12230
|View full text |Cite
|
Sign up to set email alerts
|

Musical rhythm discrimination explains individual differences in grammar skills in children

Abstract: This study considered a relation between rhythm perception skills and individual differences in phonological awareness and grammar abilities, which are two language skills crucial for academic achievement. Twenty-five typically developing 6-year-old children were given standardized assessments of rhythm perception, phonological awareness, morpho-syntactic competence, and non-verbal cognitive ability. Rhythm perception accounted for 48% of the variance in morpho-syntactic competence after controlling for non-ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
150
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(204 citation statements)
references
References 57 publications
28
150
1
1
Order By: Relevance
“…In line with this view, rhythm abilities predict phonological processing in typically developing children (Carr, White-Schwoch, Tierney, Strait, & Kraus, 2014;Moritz, Yampolsky, Papadelis, Thomson, & Wolf, 2013), adolescents (Tierney & Kraus, 2013), and adults (Grube, Cooper, & Griffiths, 2013). Such associations also extend to syntax and reading abilities (Gordon et al, 2015;Grube et al, 2013;Tierney & Kraus, 2013). For children with reading impairments, rhythm abilities are below normal (Overy, Nicolson, Fawcett, & Clarke, 2003) and correlated with their phonological and reading abilities (Huss, Verney, Fosker, Mead, & Goswami, 2011).…”
Section: Music Perception and Speech Perceptionmentioning
confidence: 74%
See 1 more Smart Citation
“…In line with this view, rhythm abilities predict phonological processing in typically developing children (Carr, White-Schwoch, Tierney, Strait, & Kraus, 2014;Moritz, Yampolsky, Papadelis, Thomson, & Wolf, 2013), adolescents (Tierney & Kraus, 2013), and adults (Grube, Cooper, & Griffiths, 2013). Such associations also extend to syntax and reading abilities (Gordon et al, 2015;Grube et al, 2013;Tierney & Kraus, 2013). For children with reading impairments, rhythm abilities are below normal (Overy, Nicolson, Fawcett, & Clarke, 2003) and correlated with their phonological and reading abilities (Huss, Verney, Fosker, Mead, & Goswami, 2011).…”
Section: Music Perception and Speech Perceptionmentioning
confidence: 74%
“…For example, melody and rhythm perception are correlated (.5 < r < .7; Bhatara et al, 2015;Wallentin et al, 2010), and in studies of non-native language (L2) abilities, researchers have reported that L2 experience predicts rhythm but not melody perception (Bhatara, Yeung, & Nazzi, 2015), melody perception is correlated positively with L2 pronunciation (Posedel, Emery, Souza, & Fountain, 2012), and better melody and rhythm abilities predict better L2 phonological abilities (Kempe, Bublitsz, & Brooks, 2015;Slevc & Miyake, 2006). Moreover, for typically developing children, melody perception predicts phonological processing (or reading ability) equally well or better than rhythm perception (Anvari, Trainor, Woodside, & Levy, 2002;Grube, Kumar, Cooper, Turton, & Griffiths, 2012), and associations between rhythm perception and phonological processing can disappear when IQ is held constant (Gordon et al, 2015). It is an open question, then, whether associations with speech perception are stronger for rhythm than for melody perception.…”
Section: Music Perception and Speech Perceptionmentioning
confidence: 99%
“…The perception of rhythmic sequences has also been linked to individual differences in grammar (Gordon et al 2015) and phonological skills (Flaugnacco et al 2014), and experience with multiple languages is linked to enhanced perception of musical rhythms (Roncaglia-Denissen et al 2016). These findings have two main translational implications.…”
Section: Translational Implicationsmentioning
confidence: 99%
“…This line of reasoning is reinforced by recent studies such as Gordon et al (2015) suggesting that there is a correlation between rhythm perception skills and morpho-syntactic production in children with typical language development (and note also that a strong association between reading skills and meter perception and rhythm processing has been found; Flaugnacco et al, 2014;). Likewise, studies like Zumbansen et al (2014), report the beneficial effects of both pitch and rhythm in the clinical therapy for patients with Broca's aphasia.…”
Section: The "Prosodic Bootstrapping" Hypothesismentioning
confidence: 66%